A novel approach for voltage secure operation using Probabilistic Neural Network in transmission network - Santi Behera; M. Tripathy; J.K. Satapathy (Journal of Electrical Systems and Information Technology, 2016)
This work proposes a unique approach for improving voltage stability limit using a Probabilistic Neural Network (PNN) classifier that gives corrective controls available in the system in the scenario of contingencies. The sensitivity of system is analyzed to identify weak buses with ENVCI evaluation approaching zero. The input to the classifier, termed as voltage stability enhancing neural network (VSENN) classifier, for training are line flows and bus voltages near the notch point of the P–V curve and the output of the VSENN is a control variable. For various contingencies the control action that improves the voltage profile as well as stability index is identified and trained accordingly. The trained VSENN is finally tested for its robustness to improve load margin and ENVCI as well, apart from trained set of operating condition of the system along with contingencies. The proposed approach is verified in IEEE 39-bus test system.